2021
DOI: 10.3389/fmicb.2021.618252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol Vapor Treatment on the Growth of Alternaria alternata and Botrytis cinerea and Defense-Related Enzymes of Fungi-Inoculated Blueberry During Storage

Abstract: The aim of the present study was to investigate the effects of ethanol vapor on the inhibition of Alternaria alternata and Botrytis cinerea in postharvest blueberry and the induction of defense-related enzymes (DREs) activities in fungi-inoculated blueberries stored at 0±0.5°C for 16days. Results indicated that ethanol vapor markedly inhibited the mycelial growth of A. alternata and B. cinerea in a dose-dependent manner, with inhibition rates of 9.1% (250μlL−1), 36.4% (500μlL−1), and 5.5% (1,000μlL−1) on A. al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…A wide range of microbial pathogens can cause the postharvest rot of blueberries, mainly Alternaria alternata , Botrytis cinerea , and Colletotrichum gloeosporioides ( Wang et al, 2010 ). Recently, it has been reported that exogenous substances such as ethanol ( Ji Y. et al, 2021 ), natamycin ( Saito et al, 2022 ), sodium nitroprusside ( Ge et al, 2019 ), and jasmonic acid methyl ester ( Wang et al, 2020a ) can minimize the postharvest rot of blueberries. The effects of these substances are mainly attributed to the inhibition of the growth of microbial pathogens via their action as fungicides or to the induction of disease resistance in fruits via their action as exogenous inducers.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of microbial pathogens can cause the postharvest rot of blueberries, mainly Alternaria alternata , Botrytis cinerea , and Colletotrichum gloeosporioides ( Wang et al, 2010 ). Recently, it has been reported that exogenous substances such as ethanol ( Ji Y. et al, 2021 ), natamycin ( Saito et al, 2022 ), sodium nitroprusside ( Ge et al, 2019 ), and jasmonic acid methyl ester ( Wang et al, 2020a ) can minimize the postharvest rot of blueberries. The effects of these substances are mainly attributed to the inhibition of the growth of microbial pathogens via their action as fungicides or to the induction of disease resistance in fruits via their action as exogenous inducers.…”
Section: Introductionmentioning
confidence: 99%
“…CHT degrades chitin, which is the major component of fungal pathogen cell walls. GLU, one of the most fully characterized pathogenesis‐related proteins, also acts indirectly by releasing an oligosaccharide and eliciting defence reactions, then acting synergistically with CHT to inhibit fungal growth (Ji et al, 2021). Here, PAL, GLU, and CHT activities were all induced by V .…”
Section: Discussionmentioning
confidence: 99%
“…Phytopathogenic microorganisms are common in nature and pose a constant threat to plants. Nonetheless, plants rarely become infected and develop disease; a multilayered innate immune system protects them from most pathogens (Johansson et al, 2015). To cope with pathogens, infected plants may deploy a rapid and strong defensive response called the hypersensitive reaction (HR) (Balint-Kurti, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Alternaria is comprised of more than 350 species which may be saprophytic, endophytic, or even pathogenic in nature [ 14 ]. This wide range of action is partly due to the ability of Alternaria to survive in low nutrient media and temperatures ranging from −3 to 35 °C [ 15 ]. Its presence has been described in countries in the temperate zone of the planet, such as China, Europe, the United States, Australia and New Zealand [ 16 , 17 ], although there are few data from Africa [ 18 ].…”
Section: Alternaria Alternata As a Plant Pathogenmentioning
confidence: 99%